High genetic diversity among extraintestinal Escherichia coli isolates in pullets and layers revealed by a longitudinal study. Issue 1 (December 2016) - Paudel, Surya; Stessl, Beatrix; Hess, Claudia; Zloch, Angelika; Hess, Michael
Abstract Background Various information about the genetic diversity ofEscherichia coli isolates from chickens are available but a detailed epidemiological investigation based upon isolates obtained from interrelated pullet and layer flocks is still missing. Therefore, in the course of a longitudinal epidemiological study on pullets and layers, 144E. coli isolates from chickens with or without pathological lesions of the reproductive tract were serotyped and genotyped with pulsed-field gel electrophoresis (PFGE). These isolates were collected during rearing, peak and at the end of production. The actual study is the first of its kind so as to elucidate genetic relatedness among extraintestinalE. coli isolated from chickens with varying pathological conditions in interrelated layer farms/flocks at different stages of rearing. Results Serotyping revealed that 63.19 % of the isolates could not be assigned to any of the three serotypes tested whereas 30.55 % of the isolates belonged to serotype O1:K1, 4.86 % to O2:K1 and 1.38 % to O78:K80. After macrorestriction digest withXba I, 91.66 % of the isolates were typeable resulting in 96 distinct PFGE profiles. Among them, five PFGE types included isolates collected from diseased chickens as well as from birds without pathological lesions. This finding shows that pathogenicity ofE. coli in layers seems to be largely influenced by concurrent susceptibility factors. Furthermore, in six out of eight cases where two isolates were collected from each of eight birds, different PFGE types were found in the same or different organs of the same bird. The existence of predominant or persistentE. coli genotypes was only observed in two cases. Conclusions It is concluded that extraintestinalE. coli genotypes and serotypes in pullets and layers are heterogenous and also do not maintain a single clonality within the same bird. The facts thatE. coli strains did not show any definite clonal population structure based on geographical region, age of the host and pathological lesions should have relevance in further epidemiological studies and control strategies.